Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.3 - Real Numbers and Algebraic Expressions - Problem Set 2.3 - Page 69: 82



Work Step by Step

First, we simplify the expression: $5x-2+6x+4$ =$5x+6x-2+4$ =$11x+2$ We evaluate the expression by substituting the value of $x=-1.1$ into the expression: $11x+2$ =$11(-1.1)+2$ =$11(-\frac{11}{10})+2$ =$-\frac{121}{10}+2$ =$-12.1+2$ =$-10.1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.